2019
DOI: 10.3390/ani9100781
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Corn Supplementation into PKC-Urea Treated Rice Straw Basal Diet on Hematological, Biochemical Indices and Serum Mineral Level in Lambs

Abstract: Simple SummaryIn Malaysia, livestock farms have used palm kernel cake as the main source of feed for livestock. The low cost and good content of crude protein in palm kernel cake makes it an appropriate food for sheep, but feeding huge amounts of palm kernel cakes (PKC) for a long period may expose them to copper toxicity. This study suggests supplementing a certain amount of corn as a source of energy into PKC basal diets estranged of toxicity to maintain the health status of lambs compared with other treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
3
4
1
Order By: Relevance
“…However, a higher concentration of dietary Cu in the sheep diet may probably cause mortality and histopathological changes within the tissues of vital organs due to toxicity. Findings from the present study are inconsistent with (Saeed et al, 2019a;Saeed et al, 2019b;Soren et al, 2017) on their studies on Cu poisoning in domesticated sheep. The histopathological findings confirm the mild liver toxicity observed in present study agrees with (Hair-Bejo et al, 1995) who reported hepatocyte swollen, as well as vacuolated and necrotized, particularly at the medulla zone.…”
Section: Discussioncontrasting
confidence: 99%
“…However, a higher concentration of dietary Cu in the sheep diet may probably cause mortality and histopathological changes within the tissues of vital organs due to toxicity. Findings from the present study are inconsistent with (Saeed et al, 2019a;Saeed et al, 2019b;Soren et al, 2017) on their studies on Cu poisoning in domesticated sheep. The histopathological findings confirm the mild liver toxicity observed in present study agrees with (Hair-Bejo et al, 1995) who reported hepatocyte swollen, as well as vacuolated and necrotized, particularly at the medulla zone.…”
Section: Discussioncontrasting
confidence: 99%
“…The MCV parameter of the sheep in the study was 30.46±3.38 fL that was considered to be in the normal limit of the textbook parameter (Byers and Kramer, 2010) at level 28.00-40.00 fL and consistent with the MCV of the sheep reported by Saeed et al(2019), which was at the level of 29.40±0.33 fL and also the MCV of the sheep with the CF supplemented with Exogenous Fibrinolytic Enzymes Cocktail, which was at the level of 27.00±0.25 fL (Beigh et al, 2018). The normal MCV parameter of the sheep in the study was consistent with the study of the sheep fed with Moringa oleifera leaf meal by (Jiwuba et al, 2016).…”
Section: Resultssupporting
confidence: 86%
“…The MCHC parameter found in the study was at the level of 34.00±1.86 g/dL and in the normal limit according to textbooks (Byers and Kramer, 2010) that was at the level of 31.00-34.00 g/dL. It was also consistent with the MCHC level of the sheep fed with the CF supplemented with Exogenous Fibrinolytic Enzymes Cocktail, which was at the level of 34.06±0.45% (Beigh et al, 2018) and with the MCH level of the sheep reported by Saeed et al (2019), which was at the level of 36.30±0.17 g/dL. The normal MCV, MCH, and MCHC levels of the fat tail sheep in the study showed that there was not any anemia indication in the sheep (Jiwuba et al, 2016) and Soul et al (2019).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Hematological indices are related to nutritional status. They have been used to monitor and evaluate animal health and nutritional status, and the cause of an abnormality or dysfunction in ruminants is often assessed through blood analysis [ 37 ]. The inclusion of YERSEK did not affect hemogram indicators.…”
Section: Discussionmentioning
confidence: 99%